Is a reunification possible on the Korean peninsula? (2013)
Since 1948, inter-Korean relations have fluctuated. Initially, reunification was sought through force and absorption, then the recovery of trust dominated the process. North Korea is increasingly isolated and in decline. Events such as the collapse of the Soviet Union system, the death of the founder of Juche, the strong famines and the change of course of its historical allies, have deeply weakened the regime that will end up collapsing at some point. Given the current situation in North Korea and the change in the attitude of the South Korean government towards an improvement in relations, it is possible to think about a reunification approaching.